The Effective Strategies To Turn Final Project Into Journal Article: Publication Transformation In Industry Trends - Br Perangin-angin, Sinek Mehuli (SEAN Institute, 2024)
Companies in the print media publishing industry have been encouraged to transform to new media by the changing media consumption patterns of audiences due to increasing technological developments. This condition eventually led to a series of consequences for the companies in the industry to transform their production and consumption processes in order to meet the needs of the society in the digital era. The same thing happened to Gramedia Magazine, where they adopted a digital transformation strategy through the transformation of the old production process into a production process integrated with an information system in the world of information technology. This dissertation tries to describe this transformation process, using the perspective of the theory of mediamorphosis, to give a view of the transformation taking place from the perspective of the publishing world as a response to technological evolution. This research uses descriptive qualitative research methods with data collection through interviews, observations, and literature reviews. The results of the study found that there were changes in strategies made in content production, resource empowerment, and technology systems with the aim of maintaining its sustainability in the publication industry in the digital age.